2020
DOI: 10.1021/acs.macromol.0c00854
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Copolymerization of Styrene Derivatives and Oxiranes via Concurrent Vinyl-Addition and Ring-Opening Mechanisms: Multiblock Copolymer Formation via Occasional Crossover Reactions

Abstract: Styrene derivatives were demonstrated to cationically copolymerize with 2,2-disubstituted oxiranes, which can generate a tertiary carbocation by the ring opening of the oxonium ion, through crossover reactions. The copolymerization proceeded with comparable consumptions of both the vinyl and cyclic monomers when appropriate combinations, such as p-methoxystyrene and 2-ethylhexyl β-methylglycidyl ether or p-methylstyrene and β-methylepichlorohydrin, in terms of reactivity were used. The homopropagation reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The C-C single bonds in vinyl polymers offer excellent stability for the intended applications, yet these polyethylene-like polymers are notoriously difficult to degrade, posing grand challenges in recycling these polymers and when degradation is desirable (e.g., drug delivery). [1][2][3] Various strategies have been developed to overcome this challenge, including copolymerization with degradable monomers, [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] introduction of degradable groups by combining with step-growth polymerization, [19][20][21][22][23][24] depolymerization to monomers under special conditions, [25][26][27][28][29][30][31] and degradation to oligomers catalyzed by special reactions. [32][33][34][35] Among them, introducing labile carbon-heteroatom bonds (e.g., ester) into vinyl polymers via copolymerization of a second monomer containing such labile bonds is one of the most efficient methods.…”
Section: Introductionmentioning
confidence: 99%
“…The C-C single bonds in vinyl polymers offer excellent stability for the intended applications, yet these polyethylene-like polymers are notoriously difficult to degrade, posing grand challenges in recycling these polymers and when degradation is desirable (e.g., drug delivery). [1][2][3] Various strategies have been developed to overcome this challenge, including copolymerization with degradable monomers, [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] introduction of degradable groups by combining with step-growth polymerization, [19][20][21][22][23][24] depolymerization to monomers under special conditions, [25][26][27][28][29][30][31] and degradation to oligomers catalyzed by special reactions. [32][33][34][35] Among them, introducing labile carbon-heteroatom bonds (e.g., ester) into vinyl polymers via copolymerization of a second monomer containing such labile bonds is one of the most efficient methods.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] In 2013, Aoshima and co-workers reported the cationic hybrid copolymerization (CHcP) of vinyl ether (VE) and alkylene oxide. [14][15][16][17][18] The rational design of monomer structures and initiation systems is the key to realize the crossover between cationic vinyl-addition polymerization of vinyl ether and cationic ring opening polymerization of alkylene oxide. Recently, You et al reported a radical/anionic hybrid copolymerization (RAHcP) by employing trithiocarbonate as both a chain transfer agent for radical reversible addition-fragmentation chain transfer polymerization of vinyl monomers and an initiator of ROP simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…[ 10–13 ] In 2013, Aoshima and co‐workers reported the cationic hybrid copolymerization (CH c P) of vinyl ether (VE) and alkylene oxide. [ 14–18 ] The rational design of monomer structures and initiation systems is the key to realize the crossover between cationic vinyl‐addition polymerization of vinyl ether and cationic ring opening polymerization of alkylene oxide. Recently, You et al.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, copolymerization of heteroatom‐containing cyclic monomers with common vinyl monomers, by which labile carbon‐heteroatom bonds can be introduced via ring opening of the cyclic structures, is one of the most efficient methods [23–26] . Various cyclic compounds, which are copolymerizable via ring‐opening reactions, have been developed to date and include cyclic ketene acetals, [27–40] thionolactones, [41–47] and cyclic allylic sulfur compounds [48–52] for radical polymerization as well as oxiranes, [53, 54] cyclic acetals, [55, 56] hemiacetal esters, [57] and 1,3‐dioxa‐2‐silacycloalkanes [58] for cationic polymerization.…”
Section: Introductionmentioning
confidence: 99%